Implementasi Kurikulum Merdeka Dalam Meningkatkan Minat Belajar Siswa pada Pelajaran PPKn - Mihbub Alam; Uswatun Hasanah; Ani Sulianti; Ribut Prastiwi Sriwijayanti (CV. ITTC INDONESIA, 2024)
The research aims to provide implications in the independent curriculum-based learning process for students' interest in learning in Civics subjects, to find out the extent to which the independent learning curriculum system influences students' interest in learning because it can indirectly be a benchmark for the world of education. This research was carried out at MTs Wali Songo 1 Maron, in February-March 2024. The research method uses a descriptive qualitative approach to find out more deeply about the implementation of the independent curriculum on students' learning interests. Data collection was obtained through interviews, observation and documentation with informants, Head of Madrasah, Deputy Head of Curriculum, Civic Education Teacher and representatives of 2 students at MTs Wali Songo 1 Maron. The results of the research show that the implementation of the independent curriculum at MTs Wali Songo 1 Maron has only been running for the 2023/2024 academic year for less than 1 year, the implementation of the independent curriculum has not been optimal, the Madrasah has not yet received a decree from the Government, but has implemented several IKM points, although not all. and the impact of implementing the independent curriculum on students' interest in learning has increased as evidenced by the fulfillment of indicators of student interest in learning, especially in Civics learning. Among them, students are happy in class, the learning process is going well. Student involvement is active in asking questions, expressing opinions, answering, discussing and even making projects or final assignments and their learning outcomes have increased significantly.